Virtual teams are here to stay: How personality traits, virtuality and leader gender impact trust in the leader and team commitment - Carlos Flavián Blanco; Miguel Guinalíu; Pau Jordán (European Research on Management and Business Economics (ERMBE), 2022)
Teleworking has, today, become a necessity for many organizations, so effective virtual team management is critical. This study analyzes the influence of the personality traits of virtual team workers on team efficiency. To do so we examine the effects of subordinates' personalities on the trust they give the virtual team leader and the impact of this trust on commitment to the team. We also discuss how the team's degree of virtuality and the leader's gender influence the relationship between personality and trust. The findings showed that extroversion has a positive effect on trust felt in the leader, and that this trust has a positive effect on commitment felt toward the team. On the other hand, it was observed that neuroticism had a more negative effect on trust in more virtual environments. The leader's gender had no significant effect. The study offers advice for virtual team management and discusses its limitations and future research directions.
Keywords: 650; Commitment; Extroversion; Gender; Neuroticism; Trust; Virtual teams; Virtuality